Carnap's Scientific Humanism - Christian Damboeck (Journal for the History of Analytical Philosophy)
Scientific humanism is the formula by which Rudolf Carnap positions science as the best tool for improving life. Science allows us to maximize the rational character of human decisions on the basis of meta-values that include epistemic values and values for rational decision making. These values are politically neutral in that they are not tied to any partisan political position, but deeply political because they allow us to avoid irrational reasoning and to make the right use of science for our political and moral decisions. Maximizing rationality does not mean, for Carnap, that we must think and calculate before every action. Rather, the overall noncognitive character of values and decisions leads to a decisionist momentum, which means that we must find the right balance, both personally and politically, between sharp thinking and following our attitudes, because science is a signpost, not a leader, in life. Carnap’s views are rooted in the intellectual currents of early twentieth-century Central Europe, including Max Weber’s scientific value-neutrality, the German Life Reform and Youth Movement, Lebensphilosophie, the decisionism of the 1920s, and the empiriocriticist branch of Austrian social democracy.